(untitled) (Global Journal of Science Frontier Research, 2016)
The helicity of stable single, double, and triple helical iodine chains inside singe-walled boron nitride nanotubes is studied using the calculation of the systematic interaction energy. The results indicate that the optimal helical radius increases linearly with the radius of the tube. Hence, there is a constant distance between the I-chain and the tube’s wall. The optimal helical angle depends on the inter-chain interaction. It is affected, however, by the tube’s confinement effect: a small opt(φ) can be induced by large inter-chain for the same tube or a large tube for the same chain structure. The helicity of the encapsulated I-chains is insensitive to the tube’s chirality but depends strongly on the tube diameter.